Drug cupping therapy and related nursing management for a cervical spondylosis patient who suffered from neck and shoulder pain (储药罐技术治疗项痹病颈肩疼痛1例的护理) - LI Yuanyuan (李媛媛); TANG Ling (唐玲); DENG Jianhua (邓建华) (中西医结合护理)
This article reviewed the effect and nursing measures of drug cupping therapy for a cervical spondylosis patient who suffered from the neck and shoulder pain. Nursing assessment, drug cupping therapy, component analysis of drug, application methods and cautions of cupping thearpy, routine nursing intervention such as dietary guidance and rehabilitation exercise were summarized. Under the guidance of the Traditional Chinese Medicine nursing by syndrome differentiation, the drug cupping therapy was adopted to relieve the neck and shoulder pain after treatment and improve the patient’s shoulder joint flexibility. (本文总结1例项痹病颈肩疼痛及肩颈活动受限患者行储药罐技术干预的护理经验, 包括护理评估、储药罐技术的操作方法和药方组成、注意事项以及饮食、康复锻炼等常规护理内容。基于中医辨证施护理论, 采取储药罐疗法并辅以相关护理措施, 能够明显减轻患者疼痛, 提高肩关节活动度。)